TO THE PROBLEM OF MILANKOVITCH PALEOCLIMATIC CYCLES - Kosov A.A. (My University, 2003)
The suggested hypothesis is in sympathy with the new concept of astronomical theory of paleoclimate (Bol'shakov and Bol'shakov, 1999) that implies a greater climatic impact of eccentricity fluctuations than it follows from the Milankovitch theory. The solar tide-producing force considerably increases (by 17%) in periods of maximum eccentricity parameter that may result in activation of volcanic activity causing greenhouse effect in the atmosphere. According to Milankovitch theory, the integral insolation of the Earth increases by 0.1% in the same periods. These two factors are favorable for synchronous climatic warming in both hemispheres of our planet.